ANALYZING MIKROTIK BASED VRRP (VIRTUAL ROUTER REDUNDANCY PROTOCOL) IMPLEMENTATION ON HOMEGRID NETWORKS - Agustini Rodiah Machdi (Universitas Pakuan, 2019)
Virtual Router Redundancy Protocol (VRRP) was developed to eliminate internal failures a single node gateway system, causing a network link to be disconnected. VRRP is capable provide redundant routing path link access. This time the research applied technology This VRRP is on a home network or building that utilizes the electricity installation network as LAN (Local Area Network) commonly called HomeGrid, and test it by doing QoS metric measurement. The QoS values obtained are then compared to the QoS standard on TIPHON as proof that network conditions are still in normal limits. The system is tested using 3 (three) schemes to get maximum results. Condition network using this VRRP system only requires very short downtime, when viewed from packet capture monitoring takes only 3 to 4 seconds in all schemes. Thus the technological capabilities of the VRRP system have been tested and are capable provide high availability linksVirtual Router Redundancy Protocol (VRRP) was developed to eliminate internal failures a single node gateway system, causing a network link to be disconnected. VRRP is capable provide redundant routing path link access. This time the research applied technology This VRRP is on a home network or building that utilizes the electricity installation network as LAN (Local Area Network) commonly called HomeGrid, and test it by doing QoS metric measurement. The QoS values obtained are then compared to the QoS standard on TIPHON as proof that network conditions are still in normal limits. The system is tested using 3 (three) schemes to get maximum results. Condition network using this VRRP system only requires very short downtime, when viewed from packet capture monitoring takes only 3 to 4 seconds in all schemes. Thus the technological capabilities of the VRRP system have been tested and are capable provide high availability linksJournal of Science Innovare is licensed under Keywords: VRRP;Mikrotik;Router;JPerf;QoS;jitter